Metodología semántica de análisis de textos literarios - Torres Ribelles, Francisco Javier (Miscelánea: A Journal of English and American Studies, 1992)
Taking into account the hypothesis that the concerns of the author of a linguistic text can be reached through stylistic features, the article claims that a semantic study of the lexical level of a text may lead to the though underlying it. After defining the nuclear and relational units necessary in the analysis, the essay goes on to suggest a practical methodology with three main stages as a way to elicit the author’s concerns: the arrangement of semantic fields, the examination of semantically related units in a disposition of syntagmatic contiguity, and the classification of deviations from the linguistic system.